Pengaruh Penerapan Manajemen Berbasis Sekolah Terhadap Peningkatan Mutu Pendidikan Di SMK Swasta Pembda Nias - Defelinu Harefa; Exaudi Ziliwu; Resman Hendi Nofanolo Harefa; M. Giatman Harefa; Ernawati Harefa (Educatio, 2025)
The application of School-Based Management (SBM) has emerged as a strategic method to enhance education quality, particularly in vocational high schools. This study investigates the influence of SBM implementation on the educational standards at SMK Swasta Pembda Nias. A quantitative approach combined with descriptive analysis was utilized to gather data through interviews, observations, and questionnaires involving principals, teachers, and administrative staff. The findings demonstrate that effective SBM practices significantly improve education quality by ensuring structured curriculum management, optimal human resource utilization, and active involvement from the community and stakeholders. Key factors contributing to success include strong school leadership, community collaboration, and adequate resource allocation. These results underscore the relevance of SBM as a vital strategy for advancing educational quality in vocational schools, particularly in regions with distinctive challenges like Nias.